Subcostal M-mode computerised echocardiography. An alternative or complementary approach to parasternal echocardiography?. Issue 1 (July 1983) - Rein, A J; Azancot, I; N'Guyen, A V; Adda, J L; Georgiopoulos, G; Piekarski, A; Slama, R
Abstract : Subcostal M-mode echocardiography has been suggested as a method for assessment of left ventricular size and function. Parasternal and subcostal measurements (direct and derived) of left ventricular function were compared in 30 healthy young subjects. We calculated instantaneous left ventricular diameter and wall thickness every 10 ms for both the subcostal and parasternal approaches using a computer program for echocardiographic digitisation and compensation. All variables were filtered to calculate instantaneous first derivative (velocity) and logarithmic derivative (normalised velocity). The program provided normal values for computerised variables of left ventricular function from the subcostal approach. It was found that there was no identity and no correlation or a poor one between subcostal and parasternal left ventricular internal diameters and volumes. The parietal wall thickness was significantly greater using the subcostal approach, and the comparative velocities study showed striking variations between the two approaches, especially in diastole, where the peak lateral wall thinning rate was 20% lower than the posterior thinning rate. We conclude that for a normal and young population, the subcostal and standard parasternal data cannot be used interchangeably for precise studies of left ventricular function. The subcostal approach, however, provides useful complementary information about lateral wall motion.